(3GdbUjOI GdWfWQGfjIs - (3GdnqWrfnWQGfj, eYjf GdOjf, CMeO Hf YHO GdQRGb, (B485 (3g`s ((3ehQhj MGaX eMeO UGOb Yhfjs)
(3ChdgG (B:s
(3jG NGdj GdHGd bO HdHdJ HGdHdHGd HGd HGdfhi RdRdJfj hGdYbd aj GdRdRGd jG QTjb GdbO bO bhSJ bOi aGSJbes
(3BNQgG (B:s
(3Oe Ydi RYe GdYOi hGQJM HYhO GdYjO aj OhdI ZQGA ajgG COhe GdCdWGa WGas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 150s
(3eYLe GdeDdajf(B: 1 / 169s
(3cTa GdXfhf(B: 2 / 1340s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs